Gingival Enlargement Induced by Felodipine Resolves with a Conventional Periodontal Treatment and Drug Modification - Nabil Khzam; David Bailey; Helen S. Yie; Mahmoud M. Bakr (Case Reports in Dentistry)
We present a case of a 47-year-old male who suffered from GE around his lower anterior teeth as soon as he started treatment with Felodipine 400 mg. We show that oral hygiene measures, antibiotics, and conventional periodontal treatment (scaling and root planing SRP) were all not sufficient to resolve the drug induced GE, which will persist and/or recur provided that systemic effect of the offending medication is still present. The condition immediately resolved after switching to a different medication. The mechanism of GE is complex and not fully understood yet. It is mainly due to overexpression of a number of growth factors due to high concentrations of calcium ions (Ca2+). This affects fibroblasts proliferation and DNA synthesis and leads to a heavy chronic inflammatory cell infiltrate. Our case was managed according to the suggested protocols in previous case studies. The unique features in our case were the immediate onset of the adverse effect after starting the medication and the absence of any underlying medical condition apart from high blood pressure. Improving the oral hygiene together with SRP and cessation of the medication resolves drug induced GE.